2019
DOI: 10.3847/2041-8213/ab2636
|View full text |Cite
|
Sign up to set email alerts
|

Rapidly Evolving Disk–Jet Coupling during Re-brightenings in the Black Hole Transient MAXI J1535−571

Abstract: The main outburst of the candidate black hole low-mass X-ray binary (BH LMXB) MAXI J1535−571 ended in 2018 May and was followed by at least five episodes of re-brightenings. We have monitored this re-brightening phenomenon at X-ray and radio wavelengths using the Neil Gehrels Swift Observatory and Australia Telescope Compact Array, respectively. The first two re-brightenings exhibited a high peak X-ray luminosity (implying a high mass accretion rate) and were observed to transition from the hard to the soft st… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 40 publications
3
38
0
Order By: Relevance
“…Finally, we found that each reflare is fainter than the preceding one (see also Parikh et al 2019a and Section 4.3 for further discussion), albeit their duration appears to remain approximately constant (∼30 days). Additionally, we observe that the disc component follows the same behaviour, as it can be inferred from both spectral and timing parameters.…”
Section: Outburst Reflares Of Maxi J1535-571: the State Transition Identificationmentioning
confidence: 65%
See 4 more Smart Citations
“…Finally, we found that each reflare is fainter than the preceding one (see also Parikh et al 2019a and Section 4.3 for further discussion), albeit their duration appears to remain approximately constant (∼30 days). Additionally, we observe that the disc component follows the same behaviour, as it can be inferred from both spectral and timing parameters.…”
Section: Outburst Reflares Of Maxi J1535-571: the State Transition Identificationmentioning
confidence: 65%
“…The reflares in J1535 also displayed hysteresis in the HID, suggesting similar state transitions that we then demonstrated with our spectral fits. Swift/XRT observations of these flares also suggested state transitions (Parikh et al 2019a); however the Swift/XRT data quality did not allow the authors to detect the hysteresis loops. The reflares hysteresis loops occur at 100 times lower luminosities than the main peak of the outburst.…”
Section: Outburst Reflares Of Maxi J1535-571: the State Transition Identificationmentioning
confidence: 95%
See 3 more Smart Citations